Clinico-Pathological and Bacteriological Insights into Colibacillosis in Broiler Chickens - Sinha, Vishal K.; Kumar, Kaushal; Gupta, Santosh K.; Kumar, Pankaj; Kumar, Manoj; Kumari, Soni (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Colibacillosis caused by Escherichia coli infection is a major bacterial disease of poultry leading to significant economic losses and potential zoonotic risk. This study investigated clinico-pathological and bacteriological aspects of the disease in broiler chickens around Patna, Bihar (India), over six months. A total of 250 suspected cases were examined through necropsy, with tissues collected for gross and histopathology. Additionally, 62 swabs (34 cloacal, 28 tracheal) and 188 organ samples were processed for bacterial isolation. Gross lesions commonly observed included fibrinous perihepatitis (57.5%) and pericarditis (52.5%), along with air sacculitis, pulmonary congestion, splenomegaly, hepatic necrosis and renal congestion. Mortality was highest in birds aged 0-2 weeks (38.1%), followed by those over 10 weeks (26.2%). Histopathology revealed hepatic degeneration and necrosis, fibrinous exudation, splenic lymphoid depletion, interstitial myocarditis and necrotizing enteritis, indicating systemic infection. Bacteriological analysis showed 101 (40.4%) samples positive for E. coli, with 59 (58.4%) confirmed through biochemical tests. The study highlights the high prevalence and systemic nature of colibacillosis, emphasizing the importance of combining pathological and bacteriological approaches for accurate diagnosis, along with improved biosecurity and management practices for effective control.